Konfigurasi Infak Sedekah, Zakat, dan Wakaf Untuk Kemandirian Umat: Sebuah Model Integratif Membangun Filantropi Islam di Era Indonesia Kontemporer - Miftahul Huda (Justicia Islamica, 2011)
This paper attempts to study the phenomenon of the typical of Indonesian Islamic philanthropy. The paper focused on efforts to develop the control or governance of Islamic philantropy professionally in Indonesian context and its response to modern reality. In this issue, this paper explores the experiences and the efforts of Modern Islamic Philanthropic Institutions, named “Yayasan Dana Sosial Al-Falah” (YDSF) Surabaya in developing various Islamic philanthropic institutions for the self-reliance and the empowerment of social community. The efforts of YDSF Surabaya is to do the integrative model for institutions such as infaq, sadaqah, zakat, waqf,  so that gave birth to Islamic philanthropy configuration that is able to further strengthen the community self-reliance in contemporary Indonesia. Integrative mechanism model between the three instruments of Islamic philanthropy both infaq, sadaqah, zakat, waqf in building and developing social funds can be done with compact design of social funds delivery, the management program of social funds asset, the program of social fund-raising,  and mix design involving the three previous designs applicably.